Performance of concrete with uncrushed palm oil shell as coarse aggregate - Tai, Kah Mon (2012)
Malaysia is one of the largest producers of palm oil, contributing about 21 million tons of oil palm products in the export sector. During the process in extracting oil palm, million tons of palm oil shells (POS) as solid wastes were generated. The natural resources of coarse aggregate may be depleted in some day, and the POS as wastes can cause the pollution. In this study, uncrushed POS as aggregate replacement in concrete was studied to determine its performances. A total of 54 concrete cubes and prisms were cast and tested. The workability, apparent dry-density, compressive strength, flexural strength of POS concrete was determined. The findings show that the compressive strength and density of POS concrete was lower than the normal weight concrete. Only the full replacement of the POS concrete was considered as lightweight concrete as the density was lower than 2000 kg/m3. Besides, a total of 4 under-reinforced concrete beams were cast with the dimensions of 125 x 150 x 1600 mm, and tested to failure under four-point loading. The behaviour of the beams were studied through their load-deflection characteristic upon loading, cracking history, and mode of failure. From the result, the flexural behaviour of POS concrete beam was almost same with the normal weight concrete. The cracking pattern of the POS concrete beam was comparable with the control beam. However, the flexural strength of the POS concrete beam was lower compared with the control beam due to the weak bonding of the POS aggregates and cement paste. Overall results indicate that the POS concrete have a sufficient compressive strength that required by the ASTM C330 for lightweight structural concrete and can be used for lightweight partition in order to reduce the member selfweight.